A Series of Pyrene‐Substituted Silicon Phthalocyanines as Near‐IR Sensitizers in Organic Ternary Solar Cells. Issue 7 (2nd February 2016) - Ke, Lili; Min, Jie; Adam, Matthias; Gasparini, Nicola; Hou, Yi; Perea, J. Darío; Chen, Wei; Zhang, Hong; Fladischer, Stefanie; Sale, Anna‐Chiara; Spiecker, Erdmann; Tykwinski, Rik R.; et al.
Abstract : An attractive method to broaden the absorption bandwidth of polymer/fullerene‐based bulk heterojunction (BHJ) solar cells is to blend near infrared (near‐IR) sensitizers into the host system. Axial substitution of silicon phthalocyanines (Pcs) opens a possibility to modify the chemical, thermodynamic, electronic, and optical properties. Different axial substitutions are already designed to modify the thermodynamic properties of Pcs, but the impact of extending the π ‐conjugation of the axial ligand on the opto‐electronic properties, as a function of the length of the alkyl spacer, has not been investigated yet. For this purpose, a novel series of pyrene‐substituted silicon phthalocyanines (SiPc‐Pys) with varying lengths of alkyl chain tethers are synthesized. The UV–vis and external quantum efficiency (EQE) results exhibit an efficient near IR sensitization up to 800 nm, clearly establishing the impact of the pyrene substitution. This yields an increase of over 20% in the short circuit current density ( J SC ) and over 50% in the power conversion efficiency (PCE) for the dye‐sensitized ternary device. Charge generation, transport properties, and microstructure are studied using different advanced technologies. Remarkably, these results provide guidance for the diverse and judicious selection of dye sensitizers to overcome the absorption limitation and achieve high efficiency ternary solar cells. Abstract : A series of silicon phthalocyanines, axially substituted by a pyrene acid group and peripherally incorporated by tert‐butyl groups, are introduced as functional near infrared (IR) sensitizers into the P3HT:PCBM system. An efficient near‐IR sensitization of up to 750 nm/800 nm and power conversion efficiency improvement up to 50% is achieved. The influence of the alkyl chain length on the performance, transport, and microstructure is extensively studied.